The Role of Public Relations in Shaping the Image of Iraqi Ministries among the Iraqi Public - Alhammad, Khalaf Lafee; Mostafa, Ahmad Anwar (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aims to determine the role of public relations in shaping the image of Iraqi ministries among the Iraqi public. Methods: The authors employed two methods: firstly, a questionnaire was administered to a sample of 400 individuals. Secondly, interviews were conducted with eight PR managers from PR departments in eight Iraqi ministries. Results: The research finds that the impact of communication methods used by PR departments in shaping the image of Iraqi ministries is low. "Social media platforms such as Facebook and Twitter" are the most important communication channels used by the public, followed by "internet websites" and "personal communications." There are statistically significant differences in the effectiveness of PR activities in shaping the image of Iraqi ministries due to gender and age variables. However, there are no statistically significant differences due to educational qualifications. Finally, there is a positive, statistically significant correlation between the effectiveness of PR activities and the image respondents have formed about those ministries. Conclusions: Public relations departments are strongly encouraged to utilize the internet and social media platforms to improve the image of Iraqi ministries. It is also recommended that PR efforts should focus more on improving the image by promoting the services provided to the public by these ministries.